Antihyperglycemic Effect of Isolated Fractions of Ceiba pentandra in Alloxan Induced Diabetic Rats - Dolui, A.K.; Das, S.; Kharat, A.R. (Asian Journal of Chemistry, 2011)
The present study investigated antihyperglycemic effect of different fractions of methanol extract of Ceiba pentandra leaves. Petroleum ether, chloroform, ethyl acetate and methanol fractions of Ceiba pentandra leaves were prepared and administered individually at different doses to different batches of rats (both normal and alloxan diabetic rats) after an overnight fast. The blood glucose levels were measured at 0, 2, 4 h, 7 and 14 days after the treatment. The methanol fraction of Ceiba pentandra at a dosage of 200 mg/kg body weight is showing maximal blood glucose lowering effect in diabetic rats. The antihyperglycemic activity of Ceiba pentandra leaves was compared with the treatment of glibenclamide, an oral hypoglycemic agent.